Progressive equations

Algebra Level 2

Consider the quadratic equation a x 2 + b x + c = 0 { ax }^{ 2 }+bx+c=0 with roots α \alpha and β \beta , and whose coefficients a , b , c a,b,c are distinct, non-zero real numbers in arithmetic progression.

If 1 α + 1 β , α + β , α 2 + β 2 \frac { 1 }{ \alpha } +\frac { 1 }{ \beta } ,\ \alpha +\beta, \ { \alpha }^{ 2 }+{ \beta }^{ 2 } form a geometric progression, find a c . \frac { a }{ c }.


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ronak Agarwal
Jul 20, 2014

a , b , c a,b,c are in Arithmetic Progression , so a + c = 2 b . a+c=2b. Since a , b , c a,b,c are non-zero, we can divide by a , a, giving 1 + c a = 2 b a . 1+\frac { c }{ a } =\frac { 2b }{ a }.

Via Vieta's Formula , the product of the roots is c a = α β \frac { c }{ a } =\alpha \beta and the sum of the roots is b a = α + β , -\frac { b }{ a } =\alpha +\beta, so we have 1 + α β = 2 ( α + β ) ( i ) . 1+\alpha \beta =-2(\alpha +\beta) \qquad (i).

Since 1 α + 1 β , α + β , α 2 + β 2 \frac { 1 }{ \alpha } +\frac { 1 }{ \beta } ,\alpha +\beta ,{ \alpha }^{ 2 }+{ \beta }^{ 2 } are in Geometric Progression , we have ( 1 α + 1 β ) ( α 2 + β 2 ) = ( α + β ) 2 . (\frac { 1 }{ \alpha } +\frac { 1 }{ \beta } )({ \alpha }^{ 2 }+{ \beta }^{ 2 })={ (\alpha +\beta ) }^{ 2 }.

This reduces to α 2 + β 2 = ( α + β ) α β . { \alpha }^{ 2 }+{ \beta }^{ 2 }={ (\alpha +\beta ) }\alpha \beta. From ( i ) , (i), we can substitute α + β = 1 + α β 2 , \alpha +\beta = -\frac{1+\alpha\beta}{2}, giving

( α + β ) 2 2 α β = ( α + β ) α β 4 ( 1 + α β ) 2 2 α β = ( 1 + α β ) 2 α β . { (\alpha }+\beta )^{ 2 }-2\alpha \beta =(\alpha +\beta )\alpha \beta \qquad \Rightarrow \qquad { { 4(1+\alpha \beta ) }^{ 2 } }-2\alpha \beta =-\frac { (1+\alpha \beta ) }{ 2 } \alpha \beta.

Solving this quadratic for α β , \alpha \beta, we have α β = 1 3 , 1 \alpha \beta =\frac { 1 }{ 3 } ,-1 but α β = 1 \alpha \beta =-1 is not possible because we can't have α + β = 0 \alpha+\beta = 0 with our geometric progression.

Thus, a c = 1 α β = 3. \frac { a }{ c } =\frac { 1 }{ \alpha \beta } =3.

I believe this answer makes a mistake in the substitution step. When squaring -1/2 you should get 1/4, not 4

Robert Thompson - 4 years, 11 months ago

Robert Thompson is correct. The product of "alpha" and "Beta" is 1/3 or 1. The solution 1 is not valid since it forces b=c and the problem states that a, b, c are distinct.

Pratima Karpe - 2 months, 2 weeks ago
Mvs Saketh
Sep 20, 2014

\frac { \alpha +\beta }{ \alpha \beta } ,\quad \alpha +\beta \quad ,\quad and\quad { \alpha }^{ 2 }+{ \beta }^{ 2 }\quad in\quad GP\\ we\quad have\quad \\ by\quad property\quad of\quad roots\\ \alpha +\beta \quad =\quad -b/a\\ \alpha \beta \quad =\quad c/a\\ { \alpha }^{ 2 }+{ \beta }^{ 2 }=\quad \frac { { b }^{ 2 }-2ac }{ { a }^{ 2 } } \\ \\ now\quad as\quad they\quad are\quad in\quad GP\\ we\quad have\quad \\ (\frac { \alpha +\beta }{ \alpha \beta } )({ \alpha }^{ 2 }+{ \beta }^{ 2 })=\quad (\alpha +\beta )\^ 2\\ \\ now\quad putting\quad their\quad values\quad in\quad terms\quad of\quad a,b,c\quad \\ and\quad then\quad using\quad b\quad =\quad (a+c)/2\quad we\quad have\quad the\quad quadratic\quad interms\quad of\quad c/a\quad as\\ \\ { z }^{ 2 }-4z+3\quad where\quad z\quad =\quad c/a\\ solving\quad we\quad get\quad z=\quad 3\quad or\quad z=1,\quad as\quad a\quad and\quad c\quad distinct,\quad and\quad if\quad we\quad assume\quad a=\quad c\quad we\quad get\quad absurd\quad results\quad for\quad roots\\ we\quad have\quad a/c\quad =3

Yes. Same way. Upvoted. :)

Keshav Tiwari - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...